Tillage Systems Modify the Soil Properties and Cassava Physiology During Drought - Ocaña Reyes, Jimmy Alcides; Paredes Espinoza, Richard; Quispe Tomas, Astrid; Díaz Chuquizuta, Henry; Ore Aquino, Zoila Luz; Agurto Piñarreta, Alex; Paz Monge, W. Michel; Lobato Galvez, Roiser Honorio; Ruiz Reyes, José G.; Zavala Solórzano, José W.; Huamani Yupanqui, Hugo Alfredo; Egoávil Jump, Gianfranco; et al. (MDPI, 2025)
The statements, opinions and data contained in all publications are solely those of the individual author(s) and contributor(s) and not of MDPI and/or the editor(s). MDPI and/or the editor(s) disclaim responsibility for any injury to people or property resulting from any ideas, methods, instructions or products referred to in the content.